Strategi Pemasaran: Bauran Promosi yang Efektif dalam Rangka Meningkatkan Penjualan Kamar Hotel Quest Simpang Lima by Aston Semarang - Priyantoro, Djarot; Listyorini, Haniek (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
The development of tourism in Indonesia is growing the hotel industry rapidly throughout the region. This development has led to fierce competition between hotel players which has caused the hotel's marketing performance to decline both the number of rooms sold, occupancy rates to hotel revenue. The purpose of this study will analyze the marketing strategies implemented, especially on the promotion mix strategy that is effective in growing room sales. This research uses a qualitative method with data collection on hotel management informants. The results showed that the Sales and Marketing department of Quest Semarang hotel has conducted a series of promotional mix strategies in order to increase room sales through 5 promotional methods. The promotions include email marketing and WA Blast; promotion with website and SEO optimization, promotion through social media Instagram, Tiktok and Youtube; promotion with sales promotion with various incentives as well as promotional publications in radio talk shows and media visits. These promotional mix activities have complemented the role of promotion and are effective in increasing room sales by direct booking, building customer loyalty, cost efficiency, increasing the visibility of hotel products and services, increasing guest reach, strengthening the brand, being more interactive, maintaining consumer loyalty, and strengthening partnerships with the media.